Caustics of the restricted three-body problem - Santos, D. E.; Martins, R. V.; Winter, O. C.; Cordeiro, R. R. (Edp Sciences S A, 1998)
Trajectories of the planar, circular, restricted three-body problem are given in the configuration space through the caustics associated to the invariant tori of quasi-periodic orbits. It is shown that the caustics of trajectories librating in any particular resonance display some features associated to that resonance. This method can be considered complementary to the Poincare surface of section method, because it provides information not accessible by the other method.
Keywords: celestial mechanics, stellar dynamics; chaos